1997
DOI: 10.1192/bjp.170.6.507
|View full text |Cite
|
Sign up to set email alerts
|

An open trial of clozapine in neuroleptic-resistant childhood-onset schizophrenia

Abstract: Clozapine may be a promising drug for the treatment of resistant childhood-onset schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 15 publications
6
21
1
1
Order By: Relevance
“…Extrapyramidal symptoms were more frequent with haloperidol and risperidone, but weight increase was greater with olanzapine. Open studies with clozapine in children and adolescents with psychotic disorder resistant to other antipsychotics (Siefen and Remschmidt, 1986;Blanz and Schmidt 1993;Frazier et al 1994;Turetz et al 1997) have reported good response. In a double-blind, controlled study comparing clozapine with haloperidol in psychotic children and adolescents, Kumra et al (2006) found a somewhat better response to clozapine, but also more severe side effects.…”
Section: Introductionmentioning
confidence: 95%
“…Extrapyramidal symptoms were more frequent with haloperidol and risperidone, but weight increase was greater with olanzapine. Open studies with clozapine in children and adolescents with psychotic disorder resistant to other antipsychotics (Siefen and Remschmidt, 1986;Blanz and Schmidt 1993;Frazier et al 1994;Turetz et al 1997) have reported good response. In a double-blind, controlled study comparing clozapine with haloperidol in psychotic children and adolescents, Kumra et al (2006) found a somewhat better response to clozapine, but also more severe side effects.…”
Section: Introductionmentioning
confidence: 95%
“…An open trial with clozapine (mean dose 227.3 6 34 mg/day) in 11 children (<13 years) with neuroleptic-resistant schizophrenia showed a clear improvement in both positive and negative symptoms, mostly occurring in the first 6 to 8 weeks. Major side effects were somnolence and drooling but not agranulocytosis (Turetz et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This would not only contravene the National Institute for Clinical Excellence guidance on atypical antipsychotics, which states that 'in individuals with evidence of treatment resistant schizophrenia clozapine should be introduced at the earliest opportunity' (National Institute for Clinical Excellence, 2002), but it would also deprive patients of a potentially unique and effective treatment. Some studies in fact suggest that its use might be worthwhile and beneficial in children and young people (Kumra et al, 1996;MacEwan & Morton, 1996;Turetz et al, 1997).…”
mentioning
confidence: 99%